Legal Regulation of Interaction of Security Service of Ukraine with Civil Society in Counteracting Terrorism (Law and Safety, 2019)
The relevance of the research is determined by the prerequisites for the rise in the levels of terrorist threats in Ukraine and the development of international terrorism. In response to these threats, the state creates protective mechanisms, increasing the level of protection of the population, since this is one of its main tasks. However, this system does not fully meet its objectives without cooperation with civil society. That is why, one of the current tasks is to unite the efforts of the state and civil society institutions in fighting against terrorism.Every citizen and civil society in the whole is a stakeholder and partner in the fight against terrorism. Citizens should be active participants. Therefore, the article provides a legal analysis of the interaction of the main agency in the state system of combating terrorist activity – the Security Service of Ukraine with civil society and clarifies the ways of implementing the state policy on counteracting terrorism.The comparative legal method of the study analyzes the source base of national law concerning the interaction of the Security Service of Ukraine with civil society in fighting against terrorism.The practical relevance of the study is determined by the ability to use the main points and conclusions of the study to further studies of the problems of the interaction of counter-terrorism actors with civil society.As a result of the analysis of the normative base on the interaction of the Security Service of Ukraine with civil society in fighting against terrorism, it can be stated about the state's efforts to implement the main points of the UN Global Counter-Terrorism Strategy. In general, Ukraine's anti-terrorist system meets international standards in the field of counteracting terrorism. However, national legislation is the subject to improvement in the field of counteracting terrorism with the involvement of civil society institutions in eliminating the conditions and causes of terrorist activity.
Keywords: civil society; interaction; counter-terrorism; subjects of the fight against terrorism